Human immunoglobulin G hinge regulates agonistic anti-CD40 immunostimulatory and antitumour activities through biophysical flexibility - Liu, Xiaobo; Zhao, Yingjie; Shi, Huan; Zhang, Yan; Yin, Xueying; Liu, Mingdong; Zhang, Huihui; He, Yongning; Lu, Boxun; Jin, Tengchuan; Li, Fubin (Nature communications, 2019)
Human immunoglobulin G (IgG) agonistic antibodies targeting costimulatory immunoreceptors represent promising cancer immunotherapies yet to be developed. Whether, and how, human IgG hinge and Fc impact on their agonistic functions have been disputed. Here, we show that different natural human IgGs confer divergent agonistic anti-CD40 immunostimulatory and antitumour activities in FcγR-humanized mice, including inactive IgG3 and superior IgG2. This divergence is primarily due to their CH1-hinges despite all human IgGs requiring Fc-FcγR binding for optimal agonistic activities. Unexpectedly, biophysical flexibility of these CH1-hinges inversely correlates with, and can modulate, their agonistic potency. Furthermore, IgG Fcs optimized for selective FcγR binding synergize with and still require IgG hinge, selected for rigidity, to confer improved anti-CD40 immunostimulatory and antitumour activities. These findings highlight the importance of both hinge rigidity and selective FcγR binding in antibody agonistic function, and the need for newer strategies to modulate antibody agonism for improved clinical application. Conserved regions of the antibody molecule impact its downstream biological effects. Here the authors show that a rigid hinge conformation increases the agonistic activity of CD40 and DR5 antibodies, distinctly from FcγR-binding, suggesting that the hinge and FcR binding regions can be separately modified to optimize therapies.